The relationship between fatigue and work stress in the operating room hospital. Tgk chik in tiro, pidie regency - Ismuntania; Kartika; Idawati; Nurlela; Yuliana (International Journal on ObGyn and Health Sciences, 2023)
The fatigue felt by nurses can have a negative impact on psychological conditions. The burden of providing nursing care with a high level of problem complexity can trigger fatigue which is difficult for nurses to accommodate, often resulting in stress. The aim is to determine the relationship between fatigue and work stress in nurses. The research method is a cross-sectional approach. The sample was 34 nurses who worked in the Surgical Room at the Regional Hospital. Tgk Chik Di Tiro. Data was collected using a questionnaire. Analysis uses chi square test. Based on the results of statistical tests, it was found that the P value < (0.05), namely 0.000, it can be said that there is a relationship between the level of fatigue and the level of stress in nurses in the surgical ward at the Tgk Chik Regional General Hospital in Tiro, Pidie Regency